Numerical assessment of reinforced concrete members incorporating recycled rubber materials - Xu,B; Bompa,DV; Elghazouli,AY; Ruiz-Teran,AM; Stafford,PJ (Engineering Structures, 2020)
This paper is concerned with the inelastic behaviour of reinforced concrete beam-column members incorporating rubber from recycled tyres. Detailed three-dimensional nonlinear numerical simulations and parametric assessmentsare carried out using finite element analysis in conjunction with concrete damage plasticity models. Validationsof the adopted nonlinear finite element procedures arecarried out against experimental results from a series of tests involvingconventional and rubberised concrete flexural members and varying levels of axial load. The influence of key parameters, such as the concrete strength, rubber content, reinforcement ratio and level of axial load, on the performance of such members, is then examined in detail.Based on the results, analytical models are proposed for predicting the strength interaction as well as the ductility characteristicsof rubberised reinforced concrete members. The findings permit the development ofdesignexpressionsfor determiningthe ultimate rotation capacityof members,usinga rotation ductility parameter, or through a suggestedplastic hinge assessment procedure. Theproposedexpressionsare shown to offer reliable estimates of strength and ductilityof reinforced rubberised concrete members,whichare suitable for practical application and implementation in codified guidance.